Regional Volume Tables of Pinus kesiya Royle ex Gord. (Based on the Data of Manipur State) - Sharma, R. P.; Jain, R. C. (Indian Forester, 1977)
Volume Tables of Pinus kesiya have been prepared by the method of liner regression The model used is V=a+b D2H. Tables based on this medel have been given.